The Effects of Single Strains and Mixtures of Probiotic Bacteria on Immune Profile in Liver, Spleen, and Peripheral Blood - Fong, Fiona Long Yan; El-Nezami, Hani; Mykkänen, Otto; Kirjavainen, Pirkka V. (Frontiers in Nutrition, 2022)
Probiotics have potential use as immunomodulators but comparative data on the immunological effects of different strains and their mixtures is very limited. The aim in this study was to characterize the effect of oral intake of different probiotic strains alone or as mixtures on systemic and organ specific immune responses. For this purpose, healthy C57BL/6 mice were perorally administered probiotics in saline or saline alone for 3 weeks. Five common probiotic strains, Lactobacillus rhamnosus species GG (LGG) and LC705, Bifidobacterium breve 99 (Bb99), Propionibacterium freudenreichii Shermanii JS (PJS) and Escheriahia coli Nissle 1917 (EcN) and two of their mixtures were tested. Livers, spleens and blood were collected for investigation. Five of the treatments increased the abundance of natural killer (NK) cells. Bifidobacterium breve 99 (Bb99) had the most prominent effect on hepatic NK cells (20.0%±1.8%). Lactobacillus rhamnosus GG (LGG) (liver: 5.8%±1.0%; spleen: 1.6%±0.4%), Bb99 (liver: 13.9%±4.3%; spleen: 10.3%±3.7%) and EcN (liver: 8.5%±3.2%; spleen: 1.0%±0.2%) increased the percentage of both hepatic and splenic T helper (TH) 17 cells. Moreover, LGG (85.5%±3.0%) and EcN (89.6%±1.2%) increased the percentage of splenic regulatory T (Treg) cells. The tested mixtures of probiotics had different immunological effects from the individual components on cell-mediated responses and cytokine production. In conclusion, our results confirm that probiotic immunomodulatory potential of probiotic bacteria is strains and organ/tissue specific and the effects of probiotic mixtures cannot be predicted based on their single constituents.